Using Figure and Concept Knowledge in Geometry - Yavuz Karpuz, Timur Koparan, Bülent Güven (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2014)
In this study, we aim to investigate how students build interaction between concepts and figure in geometry. For this purpose we developed two type data collection tool. First one called shapely is formed eight open ended question which has concepts and figure. Second one called shapeless is formed eight open ended question which has only concepts. To prepare this data collection tools’ difficulty level we took two math teachers’ opinions. Developed data collection tools were applied 120 students at 9th grade and 11th grade in Trabzon Gazi Anatolian High School. First of all we applied shapeless questions. One month later we applied shapely questions. We investigated students’ answer and the data showed that students more succeed in shapely questions than shapeless questions. We concluded that the difficulty of solving shapeless question result from students didn’t manage to draw figure representing concept knowledge or draw wrong figure, figure drawn by students can’t fulfıl generalizability condition and students who have little knowledge of concept in geometry is under the influence of prototype figure.